Family capital, social stratification, and access to higher education: An empirical study in mainland China - Tan, Qinyi; Li, Chencheng; Wu, Pei; Abbas, Safdar; Teng, Luyan (Frontiers in Psychology, 2023)
This paper employs Bourdieu’s theory of capital—focusing on family cultural, social, and economic capital—to research the early-stage mechanism through which access to higher education is formed. While all three types of capital play a significant role in acquiring higher education, most studies tend to focus on just one type of capital. In recent years, domestic scholars have also analyzed in detail the family factors affecting children’s access to higher education (CAHE); however, they have not yet explained the mechanism by which these factors influence CAHE, and authentic tests are rare. Therefore, based on existing research, this paper uses the theoretical concept of family capital to reveal how contemporary Chinese families affect their CAHE. This paper analyzes the relationship between family capital, social stratification, and access to higher education opportunities using an econometric model based on baseline data from the China Family Panel Studies (CFPS) from 2010 to 2020, with 10,318 participants, including 4,419 females and 5,899 males. The results of a binary logistic regression analysis show that the possession of family cultural and economic capital has a direct positive influence on CAHE. Children from the elite stratum often benefit more from the accumulation of family cultural capital. Moreover, although it does not form a distinct stratum, the possession of family social capital also significantly influences children’s access to higher education. Driven by China’s political, economic, and social environment, some children from the blue-collar stratum have a comparative advantage in terms of access to higher education. The possession of family capital is an important factor in the stratification of CAHE, and cultural capital is the most influential type of capital. Parents with a low level of education should be encouraged to become engaged in schools and communities to take professional courses in assisted learning, emotional counseling, decision-making, and voluntary service.